(untitled) (Social Security Management Journal, 2025)
Drug addiction remains a widespread problem that affects people of all ages, backgrounds, and socioeconomic statuses. This study highlights the current research trend on drug addiction publishing patterns and the most used author keywords. A total of 13,476 relevant documents were obtained from the Scopus database for detailed analysis. This study used several analytical tools, including Microsoft Excel for frequency analysis, VOSviewer for data visualisation, and ScientoPy for running and executing relevant publication data retrieved and analysis. The results were presented using typical bibliometric indicators such as publication growth, author keywords analysis, publishing countries and productive authors. The findings showed a significant increase in drug addiction publications since 2006, highlighting the growing relevance of drug addiction and its broader societal impacts. The top three research studies based on a country analysis show that the United States has become an active publisher, followed by China and Italy. Importantly, these studies emphasised that the scholarly practices prevalent in drug addiction research have been impressively propagated. The trends will assist researchers in recognizing various fields and identifying the core areas, proactive institutions, and productive authors published in this knowledge for supplementary investigation. Furthermore, by examining the most popular keywords, the findings of this study enabled researchers to identify potential areas for future research, particularly in drug use prevention, laws and government policies to prevent the rising rate of addiction, and improved social well-being in comparison to drug use, which could be studied in the last five years.